Karya Tari Siksa Raga sebagai Pelahiran dari Parakang di Kabupaten Tulang Bawang - Dea Rosmaya; Donny Osmond (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dance work "Siksa Raga" is the artist's interpretation and imagination which is translated into a new dance work about the bodily reactions of parakang victims of black magic. One of the bodily reactions to parakang black magic is convulsions. To visualize the idea in this work, the creator uses stiff, vibrating body movements, jerks in the body and imbalance in the dancer's muscles, brain and body. The methods used are data collection and field observation, movement exploration, improvisation, formation and evaluation. This work was created in three parts showing the shape of the seizure. The theme used in this work chooses the theme of body space with an abstract type. This work is danced by seven female dancers and is displayed in the Boestanul Arifin Adam Auditorium building.